2008
DOI: 10.1016/j.jpsychores.2008.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Physical health status assessed during hospitalization for acute coronary syndrome predicts mortality 12 months later

Abstract: Objective: Self-report measures of health status predict mortality in several groups of patients with cardiovascular disease, although overlap with symptoms of depression may reduce or eliminate this relationship. The association between self-reported health status and mortality has not been examined in patients hospitalized for acute coronary syndrome (ACS). The objective was to investigate whether the Physical Component Summary (PCS) and Mental Component Summary (MCS) scores of the SF-12 predicted 12-month a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…The reliability and validity of the SF-12 has been well documented (Gandek et al, 1998;Ware et al, 1996). Importantly, the SF-12 is known to be a good predictor of objective health outcomes including risk of hospitalisation and mortality, demonstrating that it provides useful information on health (Dorr et al, 2006;Thombs et al, 2008). In this study, Cronbach's a was 0.84 for SF-12 Physical and 0.88 for SF-12 Mental .…”
Section: Self-reported Healthmentioning
confidence: 58%
“…The reliability and validity of the SF-12 has been well documented (Gandek et al, 1998;Ware et al, 1996). Importantly, the SF-12 is known to be a good predictor of objective health outcomes including risk of hospitalisation and mortality, demonstrating that it provides useful information on health (Dorr et al, 2006;Thombs et al, 2008). In this study, Cronbach's a was 0.84 for SF-12 Physical and 0.88 for SF-12 Mental .…”
Section: Self-reported Healthmentioning
confidence: 58%
“…However, the single-item measures used in this study had been previously used and validated in other research 31,32. The health status item in particular has demonstrated strong predictive validity with self-care behaviors,33 objective indicators of health,33,58 and mortality;34,59 has been used as a dependent variable in path analytic models;54,60 and does not violate SEM assumptions for endogenous variables 38…”
Section: Discussionmentioning
confidence: 98%
“…This is further corroborated by recent evidence that depression interventions following AMI have no impact on survival [14]. Prior studies have explored the relationship between depression, self-reported health status and mortality [15,16]. However, such studies have incorporated general health status and quality of life measures [17].…”
Section: Introductionmentioning
confidence: 80%